Risk propagation mechanism: Qingdao Crude Oil Leaking and Explosion case study. (October 2015) - Liu, Hongyong; He, Weitao; Guo, Ji; Huang, Qiushuang
Highlights: The mechanism of the accident risk conduction is revealed by diagrammatic sketch. The cause of the accident is superposition of project participants' risk behaviors. The essence and cause for project participants' risk behaviors is determined. The control measures to project participants' risk behaviors are proposed. Abstract: Due to China's acceleration of urbanization expansion, more and more oil/natural gas transmission pipelines, which were originally laid in the urban outskirts, are now in the densely populated urban areas. Therefore, the urban pipeline network security risks in its operation phase are more and more common. And more and more problems are caused. Using the disaster of "Qingdao Crude Oil Leaking and Explosion" as a case study to analyze the inherent principle of risk conduction conducted by the project participants' behavior, On the basis of the perspective of information economics and engineering philosophy, the origin and essences of principal participants' risk behavior in the operational stage are revealed. Although there is no transaction behavior in the operation of urban crude oil and natural gas pipeline, the underlying causes of project participants' risk behaviors are the adverse selection due to information asymmetry, and the opportunistic actions induced by moral risks between the government supervision departments and oil and gas pipeline network operation enterprises, relevant government departments and residents. Finally, found that the nature of the main behavioral risk is asymmetric information and a lack of engineering ethics.